Evaluating the Impact of Nitrogen Application on Growth and Productivity of Maize Under Control Conditions - Hammad, Hafiz Mohkum; Chawla, M. Shakeel; Jawad, Rashid; Alhuqail, Asma; Bakhat, Hafiz Faiq; Farhad, Wajid; Khan, Faheema; Mubeen, Muhammad; Shah, Adnan N.; Liu, Ke; Harrison, Matthew T.; Saud, Shah; et al. (Frontiers in Plant Science, 2022)
Climatic conditions significantly affect maize productivity. Among abiotic factors, nitrogen (N) fertilizer and temperature are the two important factors which dominantly affect maize (Zea mays L) production during early crop growth stages. Two experiments were conducted to determine the impact of N fertilizer and temperature on the maize growth and yield. In Tthe first experiment, maize hybrids was were screened conducted to screen for their sensitivity to temperature resistance and sensitivevariations maize hybrids. The screening was based on the growth performance of the hybrids under different three temperatures (T1 = ambient open-air temperature, T2 ≈ 1 °C higher than the ambient temperature and T3 ≈ 1 °C lower than the ambient temperature) range. The results showed increase in temperature resulted less 50% emergence and mean emergence (4.1 and 6.3 days respectively), while emergence energy and full emergence were higher (25.4 and 75.2% respectively) under the higher temperature applicationexposure. The results showed that Syngenta 7720 and Muqabla S 25W87 were temperature tolerant and sensitive maize hybrids, respectively. The second experiment was carried out to study the response of the two selected maize hybrids (Syngenta 7720 and Muqabla S 25W87) to four N fertilizer applications. The results revealed that the maximum N use efficiency (19.5 kg kg-1) was achieved in maize hybrids that were fed undergiven lesswith low N application rates (75 kg N ha-1 equivalent to 1.13 g N plant-1,). However, the maximum maize grain yield (86.4 g plant-1), dry weight (203 g plant-1) and grain protein content (15.0%) were observed in maize hybrids that were grown by with the application of 300 kg N ha-1 (equivalent to 4.52 g N plant-1). Therefore, it is recommended the application of 300 kg N ha-1 to temperature tolerant maize hybrid may be considered best agricultural management practices for obtaining optimum maize grain yield under present changing climate.